A global analysis approach for investigating structural resilience in urban drainage systems. (15th September 2015) - Mugume, Seith N.; Gomez, Diego E.; Fu, Guangtao; Farmani, Raziyeh; Butler, David
Abstract: Building resilience in urban drainage systems requires consideration of a wide range of threats that contribute to urban flooding. Existing hydraulic reliability based approaches have focused on quantifying functional failure caused by extreme rainfall or increase in dry weather flows that lead to hydraulic overloading of the system. Such approaches however, do not fully explore the full system failure scenario space due to exclusion of crucial threats such as equipment malfunction, pipe collapse and blockage that can also lead to urban flooding. In this research, a new analytical approach based on global resilience analysis is investigated and applied to systematically evaluate the performance of an urban drainage system when subjected to a wide range of structural failure scenarios resulting from random cumulative link failure. Link failure envelopes, which represent the resulting loss of system functionality (impacts) are determined by computing the upper and lower limits of the simulation results for total flood volume (failure magnitude) and average flood duration (failure duration) at each link failure level. A new resilience index that combines the failure magnitude and duration into a single metric is applied to quantify system residual functionality at each considered link failure level. With this approach, resilience has been tested and characterised for an existing urban drainage system in Kampala city, Uganda. In addition, the effectiveness of potential adaptation strategies in enhancing its resilience to cumulative link failure has been tested. Graphical abstract: Highlights: Quantitative evaluation of both hydraulic and structural failures in urban drainage systems. Investigation of a wide range of sewer failure scenarios with reduced computational complexity. Simulation of 49, 200 random structural failure scenarios to determine link failure envelopes. Development of a new resilience index for quantifying system residual functionality. Effectiveness of adaptation strategies in improving structural resilience tested.